EMBLEMATIC CODE OF BAROQUE’S RHETORIC - Солецький, О. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The functionality of emblematic patterns in baroque’s poetics has been the main business of the present paper. The emblematic pattern is treated as a philosophy of the culture’s significance communication in XVII–XVIII c., manifested in the literary, religious, and educational domains. The structure interplay of visual and verbal components is reduced in a particular rhetoric type which became the foundation of meaning expression for a lot of baroques’ poets.